Fiber reinforced polypropylene composites interfacial behavior improvement fabricated by cold plasma jet SiOx nanoparticles deposition. (March 2023) - Zhang, Lin; Xia, Zhangchuan; He, Yadong; Xin, Chunling; Yu, Yang; Ren, Feng; Wang, Ruixue
In this study, cold atmospheric pressure plasma jet was adopted to glass fibers surface modification with tetraethyl orthosilicate as a precursor. To enhance the interfacial bonding forces of glass fiber reinforced polypropylene (GFRP) composites, SiOx nanoparticles were polymerized on the fiber surfaces. The effect of two factors (the distance between nozzle and fiber (D) and the treatment time (T)) on the interfacial bonding behavior of GFRP composites was studied. The modified fibers and composites properties, including surface topography, chemical composition, wettability and interfacial mechanical properties, were studied comprehensively. The optimal parameters were obtained at D = 17 mm and T = 12 s. Our results indicated that the interlaminar shear strength of GFRP composites was increased by 30.79% compared to control group. Further studies found that plasma treatment introduced larger surface roughness, surface energy and more oxygen-containing functional groups, which was responsible for the interlaminar shear strength improvement.